REPRESENTASI FILM SEBAGAI DIPLOMASI BUDAYA (ANALISIS SEMIOTIKA BARTHES FILM ME VS MAMI SEBAGAI DIPLOMASI BUDAYA PADANG) - Christina Christina; Lim Yudhi (SEMIOTIKA: Jurnal Komunikasi, 2017)
Entertainment industry is growing along with the development of communication technology especially in the film industry. Various films are created with a specific discourse or agenda. Not apart from the effort to introduce a culture, propaganda, tourism and so forth. One of the interesting things is cultural diplomacy that is done through a movie. Like one example of Me vs. Mami film that seeks to introduce Padang culture. With semiotics analysis Roland Barthes, the researchers are interested to see the representation posed in film scenes to introduce Padang culture as a form of cultural diplomacy.Keywords : Film, Cultural Diplomacy, Roland Barthes Semiotics